Effect of temporary cement on the color of temporary crowns made by conventional pressing methods and substractive CAM/CAD technologies = Efecto del cemento temporal sobre el color de las coronas temporales realizadas mediante métodos de prensado convencionales y tecnologías sustractivas CAM/CAD - Firouz, Farnaz
The color stability of temporary restoration is crucial, especially in sensitive areas in terms of aesthetics. This research aimed to determine the effect of temporary cement on the color of temporary crowns made by conventional pressing methods (indirect) and CAM/CAD technologies using milling machines and 3D printers. This study was carried out in a laboratory, utilizing A2 color in all manufacturing methods. The color of the restorations was measured by a spectrophotometer after cementation with semi-permanent resin cement. Subsequently, color changes of the samples (ranging from 0 to 100) were calculated using the Commission International de l'Eclairage (CIE) Lab system. Data analysis was based on descriptive statistics methods and statistical tests, including one-way analysis of variance (ANOVA) and Tukey's post hoc test. According to the results of ANOVA, there was a significant difference between the three groups in terms of the 'a' and 'b' indexes (P<0.001). However, regarding the 'l' index, no significant difference was observed among the three groups (P=0.250). Also, based on Tukey's post hoc test, a significant relationship was seen between the first and second pairs in the 3D printer group, and between the first and third pairs in the milling group (P<0.001). However, no significant difference was observed in the conventional pressing group. The results showed that the 3D printing method exhibited the highest amount of color change among the three methods, while the milling method demonstrated the lowest amount of change.